Theoretical Study of Density Distributions and Size Radii of 8B and 17Ne - Ridha, Arkan R.; Abbas, Zaid M. (Iraqi Journal of Science, 2018)
The proton, neutron and matter density distributions, the corresponding size radii and elastic electron scattering form factors of one-proton8B and two-proton 17Ne halo nuclei are calculated. The theoretical technique used to fulfill calculations is by assuming that both nuclei under study are composed of two main parts; the first is the compact core and the second is the unstable halo part. The single-particle radial wavefunctions of harmonic-oscillator (HO) and Woods-Saxon (WS) potentials are used to study core and halo parts, respectively. And other approach is studied by using HO potential for both core and halo parts, but using two HO size parameters for both supposed parts. The long tail behavior which is the main characteristic of halo nuclei are well produced for both 8B and 17Ne. The calculated size radii are in general in good agreement with the available experimental data. The electron scattering form factors of the C0+C2 and C0 components are also calculated for 8B and 17Ne, respectively and compared with corresponding stable 10B and 20Ne nuclei. For 8B calculations, the core-polarization (CP) effects are taken into account by using Tassie and Bohr-Mottelson models. The contribution from model-space (MS) part C2 component is taken through pwt interaction. The results of the calculated charge form factors are left for the planned electron-radioactive ion beam colliders where the study of skin or halo on the charge form factors are going to be studied.